Herpesvirus infections, antiviral treatment, and the risk of dementia—a registry‐based cohort study in Sweden - Lopatko Lindman, Karin; Hemmingsson, Eva‐Stina; Weidung, Bodil; Brännström, Jon; Josefsson, Maria; Olsson, Jan; Elgh, Fredrik; Nordström, Peter; Lövheim, Hugo (Alzheimer's & dementia : translational research & clinical interventions, 2021)
Introduction Herpesviruses, including Herpes simplex virus type 1 (HSV1) and varicella zoster‐virus (VZV), have been implicated in Alzheimer's disease (AD) development. Likewise, antiviral treatment has been suggested to protect against dementia development in herpes‐infected individuals. Methods The study enrolled 265,172 subjects aged ≥ 50 years, with diagnoses of VZV or HSV, or prescribed antiviral drugs between 31 December 2005 and 31 December 2017. Controls were matched in a 1:1 ratio by sex and birth year. Results Antiviral treatment was associated with decreased risk of dementia (adjusted hazard ratio [HR] 0.89, 95% confidence interval [CI] 0.86 to 0.92), while herpes infection without antiviral drugs increased the risk of dementia (adjusted HR 1.50, 95% CI 1.29 to 1.74). Discussion Antiviral treatment was associated with a reduced long‐term risk of dementia among individuals with overt signs of herpes infection. This is consistent with earlier findings indicating that herpesviruses are involved in the pathogenesis of AD.